SUPPLEMENTATION OF SPIRULINA AND VITAMIN C ATTENUATED THE NEPHROTOXICITY INDUCED BY CISPLATIN ADMINISTRATION - Munjal, Charu; Bhattacharyya, Shalmoli (International Journal of Research -GRANTHAALAYAH, 2016)
Overexposure of the kidneys to cisplatin [Cisplatin (cis- diaminedichloroplatinum II) (CDDP)] and cisplatin complexes cause degradation of the renal cells, and eventually lead to renal failure. Agents like antioxidants, modulators of nitric oxide (NO) and anti-apoptotic molecules are reported to reduce nephrotoxicity. In the present study we tested the hypothesis that supplementation of antioxidant spirulina and vitamin c reduces cisplatin induced nephrotoxicity. The study was carried out on female Balb /C mice of the following five groups: control (i); cisplatin (ii); vitamin c (iii); spirulina (iv); and vitamin c + spirulina + cisplatin (v). Plasma urea and creatinine levels were estimated 3 and 6 days after the injection of cisplatin and uptake studies with 99m Technician-ethylene dicysteine was performed to assess the renal clearance rate. Kidneys were isolated and processed for electron microscopy and light microscopy. The activity and concentration of antioxidant enzymes such as glutathione, catalase, superoxide dismutase and GST was also determined. Dual supplementation of spirulina and vitamin c significantly protected cisplatin-induced increased levels of serum urea, creatinine, improved renal clearance rate, the declined renal antioxidant enzymes and increased LPO levels. Hence, we conclude that supplementation of spirulina and vitamin c had a beneficial effect on cisplatin induced nephrotoxicity in mice.